PENDIDIKAN GIZI GEMAR MAKAN IKAN ANAK USIA 12-15 TAHUN SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA ALUE AMBANG KABUPATEN ACEH JAYA - Teguh Raharja; Nabila Ukthy; Yasrizal Yasrizal (Marine Kreatif, 2022)
Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. Stunting in toddlers needs special attention because it can hamper the physical and mental development of children. One way to prevent stunting can be done through increasing the amount of fish consumption. The purpose of this activity is to introduce the benefits of consuming fish to children aged 12-15 years. The stages used in this activity are giving a pre-test, socializing the benefits of consuming fish and giving a post-test. The achievement of this activity is that before the campaign it was known that the level of good knowledge of children was 50% good and 50% less. Meanwhile, after the campaign there was a change in the level of children's knowledge increased by 100% which was good and 0% which was less. So it can be concluded that the campaign for eating fish has a significant effect on the level of knowledge of children.